Attitude of Mothers Toward Home Management of Acute Diarrhea in Children Under Five Years of Age - AL Bashir, Somia I.; Altamimi, Noora B.; Alharbi, Nada Reda; Alrashidi, Amani F.; Alshamary, Entesar; Al-Rashidi, Khyryh; Alanzi, Seham S. (Arab Journal for Sciences and Research Publishing, 2016)
A descriptive study conducted in Hail city (north-western Saudi Arabia, has a population of 412.758 according to Ha’il Province in 2010). Study aim to assess knowledge of mother about acute diarrhea in children under five years in Hail city (north-western Saudi Arabia), and to assess the attitude of mothers of home management of acute diarrhea. A questionnaire was used to collect data from 522 mothers of children under five years old whom suffered from diarrhea during the last year were included in the study. Mothers whose children didn’t have diarrhea during the last year were excluded. Questionnaires were distributed directly to the mothers and through social media. The data were statistically analyzed using SPSS 19 program for Windows. The study started from October 2015 to February 2016, that included 522 mothers, most of the mothers are educated, and half of them were between 21-30 years of age. 37.4% of mothers increase fluid during diarrhea, most of them gives artificial feeding only. Also, half of the children showed sign of dehydration. It’s concluded that considerable number of mothers have unfavorable attitude towards the management of acute diarrhea at home. So, they need health education.